Bibliometric Analysis of Carbon Accounting Research - Kuriawan, Kurniawan; Subowo, Hery; Firmansyah, Irman (International Journal of Energy Economics and Policy, 2022)
The issue of the environment continues to receive special attention from researchers. This is related to business operations' importance in paying attention to the profit aspect and environmental impacts to maintain the surrounding environment. Therefore, activities that affect carbon emissions must be reported annually. This is called carbon accounting. This study aims to map carbon accounting articles for 2012 to 2021 on the dimensions.ai database. Using the keyword 'carbon accounting', the collected data was 500 articles. The study results found that the journal most relevant to carbon accounting is ‘The Science of the Total Environment’. Meanwhile, the journals that have the most significant impact are ‘Global Change Biology’, ‘Scientific Reports’, and ‘The Science of the Total Environment’. Meanwhile, the most productive journal is ‘The Science of the Total Environment’, followed by ‘Environmental Science and Pollution Research’. The most relevant and prolific authors were Wang Y, followed by Zhang Y and Zhang X. In addition, Wang Y and Zhang X were the authors who had the greatest impact. The distribution of words in articles with the theme of carbon accounting is dominated by 'carbon' and 'accounting'. This research shows that the theme is undergoing good development. Research data shows that the word 'carbon' is rapidly from 2012 to 2021. This study predicts that articles on carbon accounting will continue to increase in the years to come, especially the themes of 'emissions' and 'study' which have high development although their relevance is quite low. The development of research on carbon accounting is closely related to environmental issues which are currently being studied by many researchers, especially to achieve sustainable development goals.